Engaging with Nature in Times of Rapid Environmental Change: Vulnerability, Sentience, and Autonomy - Heyd, Thomas (The Trumpeter)

(untitled) (Athabasca University Press, 2023)
Increasingly rapid environmental changes since the middle of the 20th century pose a significant challenge for vulnerable human populations. North American Native people from the Northwest Coast, as many other indigenous populations around the globe, have conceived landscapes as sentient, and capable of responding to human action. The consequent “social responsibility” taken for landscape is explored in the context of vulnerability to rapid environmental change. The basis for respect that underlies this sense of responsibility, and its significance for addressing human vulnerability to nature’s agency, through more adequate practices of mitigation and adaptation, is discussed. It is concluded that we face an imperative to reconceive the agency of natural phenomena.